2006
DOI: 10.1364/ol.32.000065
|View full text |Cite
|
Sign up to set email alerts
|

Strong enhancement and extinction of single harmonic intensity in the mid- and end-plateau regions of the high harmonics generated in weakly excited laser plasmas

Abstract: Strong intensity enhancement or extinction of some single harmonics is observed in high-harmonic generation from 48 fs Ti:sapphire laser pulses propagating through preformed low-excited laser-produced plasmas of various materials (GaAs, Cr, InSb, stainless steel). The intensities of some of the harmonics in the mid- and end-plateau regions vary from ~23-fold enhancement to near disappearance compared with those of the neighboring ones. It is also shown that the observed intensity enhancement (or extinction) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 12 publications
7
45
2
Order By: Relevance
“…This was confirmed in multiple studies following the initial observation of this phenomenon in indium plasma [19]. In particular, strong enhancement of a single harmonic was reported in Cr [20] and Mn [9] plasmas. The Mn plasma is of special interest since it showed the highest harmonic cut-off energy observed in plasma plumes (101 st harmonic of Ti:sapphire laser [9]).…”
Section: Isolated Sub-femtosecond Xuv Pulse Generation In Mn Plasmasupporting
confidence: 63%
“…This was confirmed in multiple studies following the initial observation of this phenomenon in indium plasma [19]. In particular, strong enhancement of a single harmonic was reported in Cr [20] and Mn [9] plasmas. The Mn plasma is of special interest since it showed the highest harmonic cut-off energy observed in plasma plumes (101 st harmonic of Ti:sapphire laser [9]).…”
Section: Isolated Sub-femtosecond Xuv Pulse Generation In Mn Plasmasupporting
confidence: 63%
“…We conclude that in our case the resonant enhancement of the macroscopic HH emission is dominated by reduced absorption due to Fano-resonances in the photoabsorption spectrum of the generation medium. Notably, the enhancement mechanism is of different nature than what has previously been observed for various transitionmetal ions [15,16].…”
Section: Fig 1 (Color Online)mentioning
confidence: 60%
“…In particular, Ganeev et al observed a significant resonant enhancement of a single harmonic order in laser-generated indium plasma plumes [15,16] which they attribute to resonant transitions between autoionizing states and the ground state of singly charged…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When laser pulse duration was varied from unchirped 48 fs to negatively chirped 250 fs, intensity of 13 th harmonic became comparable to that of its neighbors. These observations indicate that intensity enhancement 11) occurs due to resonance of the harmonic wavelength with one of the transitions in the atoms/ions of the plasma. Similarly extinction 11) was also seen in plasma plumes from other targets.…”
Section: High Order Harmonic Generationmentioning
confidence: 83%